Proyecto de factibilidad para la creación de una empresa para elaboración y comercialización de una bebida hidratante a base de suero lácteo, en la ciudad de Loja - Espejo Pinzón, Mariuxi Liceth (2016)
Today large companies located in developed countries seek to innovate business ideas, so they are always in constant research and studies of different products found in nature that are beneficial to health and also generate economic returns. Whereby the beverage market has experienced a major expansion in recent years, due to increased demands from consumers to obtain products that meet their needs and also provide an easy and convenient way to ensure that their organizations have adequate supply nutrient. Considering that in Ecuador dairies are very important and represents a major source of income for traders of dairy products, it has been considered to use a byproduct of the industry such as the whey obtained from the cheesemaking it contains important nutrients, approximately 55% of the original milk nutrients, determining that for every kilo of cheese produced, about five liters of serum, which represents between 80% and 90% of the volume is discarded milk, so was born the idea to use this raw material in the manufacture of a sports drink based on whey, to prevent further wasting its nutritional properties that favor the health of consumers and contribute equally to the environment. That is why this paper entitled "PROJECT FEASIBILITY FOR THE CREATION OF A COMPANY FOR PROCESSING AND MARKETING OF A MOISTURE based drink milk serum, in the city of Loja", aims to provide a quality product with a high value nutritious, at a low cost and likewise take advantage of business opportunities and business development within the market that have not yet been explored. 7 For this a methodology based on the different research methods and techniques such as deductive method, which allowed the construction of the theoretical framework, which is what directs research to give form and substance to the theoretical framework of the project is applied; the inductive method by which served for the general conclusions based on the data obtained through research techniques; the analytical method, through which was analyzed and synthesized the information collected by the instruments used for development work; mathematical method, was used to perform all mathematical operations required at different stages of the project; and the statistical method by which it could present information gathered through statistical table and graphs for better understanding of the research; The technique used was the survey was used to gather specific information on the demand and supply. Among the results of the market study, which was conducted through surveys of both plaintiffs and bidders, allowed an analysis of supply and demand, so it was determined that for the first year there is an effective demand of 713 739 liters of sports drink and an offer of 221,449 liters, so you get that unmet demand is 492,290 liters of sports drink for the first year. Likewise, the installed capacity of the company to the development of sports drink based on whey will 2.102.400litros year and capacity utilization is 250,560 liters per year, equivalent to 501 120 units of 500ml. The company will be located in the industrial park of the city of Loja, industry Amable Maria parish El Valle. The company will be formed as a limited liability company, just as organic, functional and positional structure, and the proposed manual functions was established. 8 The investment is $ 120,174.11 US dollars, the same that will be financed by the partners 58.39% and 41.61% with a loan to the National Finance Corporation, with an interest rate of 10.5% annually. The unit cost of production for the first year will be $ 0.29 cents, increasing a profit margin of 35%, resulting in a retail price of 0.39 cents, gaining sales revenue of $ 156.848,94 dollars in the first year. Financial evaluation determined that the net present value is positive ie $ 37.187,02; the internal rate of return is 19,93% indicating that is greater than the cost of capital; Benefit Cost Ratio shows that for every dollar invested in the project, generates 0.52cents useful; the Capital Recovery Period is 3 years 7, months and 17 days; finally Sensitivity Analysis with increased costs can be determined that the same increase in 21,05%, giving a total of 0.99%, also the sensitivity analysis determined decrease in revenues that may be a decrease 13,94%, totaling 0.99%. Therefore according to the results the project is feasible. After completing studies conclusions and recommendations based on the results in the development of projects are determined.